Suplemento alimentar para leitões no período de transição pós-desmama: desempenho, comportamento, morfometria e microbiota intestinal - Klein, Daniela Regina (2023)
Post-weaning is one of the most stressful periods in pigs' lives, either due to the removal from the mother, adaptation to a new environment or different litters piglets, and the challenge to adapt to a solid diet and vegetable ingredients. The aims of the present thesis were to compare the performance, intestinal histology and feeding behaviour in piglets supplemented with milk replacer, and with a meta-analysis evaluate the effects of diet characteristics and composition on postweaning piglets gut microbiota. A literature review summarised the composition of the microbiome, the importance for health, and the influence of feed, stress situations, and growth promoters and antimicrobials on weaned piglets gut microbiota. For the second article, two experiments evaluated the effect of a milk replacer supplementation for newly weaned piglets, for three and four days, on performance, intestinal morphology and health, and behaviour. In the third article a meta-analysis analysed the effect of diet characteristics and composition on gut microbiota composition. The composition of piglets gut microbiota influenced the health, nutrition and performance and, its modulation by feeding or feed additives showed promising results, which contributed to the health, performance and also reduce antimicrobials use in animal production. The experiments of the second article, using piglets weaned at 21 and 30 days of age, feeding two diets: solid feed; and solid feed + milk replacer for four and three days after weaning. The milk replacer supplementation to post-weaning piglets did not affect performance, diarrhoea index or behaviour. Piglets supplemented with milk replacer intake more feed on the second and third days after weaning, and had longer duodenal villus and larger Peyer's patches. In the meta-analysis study were evaluated the gut microbiota modulating feed additives, diet characteristics and composition effects on the main phylum of weaned piglets gut microbiota. The most abundant phylum in weaned piglets gut microbiota composition were Firmicutes and Bacteroidetes, which was not influenced by modulating feed additives. Diets with barley, wheat and rice showed an effect on the abundance of the phylum Bacteroidetes and Actinobacteria. Piglets which had intake a higher amount of protein showed a higher abundance of the phylum Firmicutes, and in those intakes lower protein the phylum Bacteroidetes was more abundant. Animals that intake less metabolizable energy had higher abundance of Firmicutes in gut microbiota